Aspectos éticos na doação de órgãos: percepção dos familiares de pacientes com morte encefálica - Amorim, Tatiana Lima (2013)
The possibility of substituting organs and tissues which are damaged with others which have their vital functions working adequately for the human body, takes place for one main reason, to preserve the health of the person seeking a longer life and mainly to propitiate a better quality of life. This paper deals with the subject of organ donation, where the theme will be explored relating it to the family‟s perception of brain death and the impediments for donation, having as its main goal to get to know the main difficulties and factors which impede relatives of brain dead patients to authorize organ donation. 66 patient records of probable donors (brain dead patients) were analyzed, 36 of which were from the year 2010 and 30 from the year 2011. However, of the 66 likely donors, organs of only 16 patients were donated. There were no donations from the other probable donors (50 patients). The families refused. 46% alleged that they did not have information about what was happening, that there was little dialog of the professionals with the family and mainly, that the initial service in the emergency room was not humanized. Many doubts afflict the families in the whole process with regard to brain death, to liberating the body and other questions which arise. If the health team clarifies and informs the family adequately there will be greater satisfaction with regard to the service rendered during the patient‟s period of internment, propitiating comfort for the families and consequently helping to diminish the pain and suffering.